Morphological Appearance of M3 Generation Mutant Strains of Brown Rice (G16) to Support Rice Seedingi in Upland - Ria Ayu Chandraningsih; Taufik Fauzi; Suwardji; Anak Agung Ketut Sudharmawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Brown rice local cultivars are found in West Nusa Tenggara, but brown rice is still very rare to be used as a source of genetic diversity and its improvement is also lacking to be considered. This research aims to determine the effect of 300 Gy gamma ray irradiation on the quantitative properties of third generation G16 brown rice (M3) in the uplands. In this research, an experimental method was used with field experiments from May to December 2022 in Tatar Hamlet, Nyurlembang Village, Narmada District, West Lombok Regency. This research used Randomized Block Design (RBD) in an Augmented design with 18 treatments consisting of 15 G16 mutant strains and 3 comparison plants. The data obtained were analyzed using Analysis of Variance (Anova) with a level of 5%, then the real different treatment was further tested using the Least Significance Different (LSD) test. Based on the results of the research, it was obtained that some of the quantitative traits observed did not have differences in the properties of the elders and their comparators. The morphological apperance of mutant plants is the same as that of both the elders and the comparison varieties. However, it can be said that all strains based on their morphological appearance have the potential to be developed on dry land, because all strains tested show the same results compared to their elders and peers.